A MODEL FOR MANAGING MEDICAL IMAGE DATA ON THE CLOUD - Al-Badarneh, Amer; Husari, Ghaith; Najadat, Hassan (LIFE: International Journal of Health and Life-Sciences, 2016)
Due to the increasing demand on Hospital Information System (HIS) resources and the high cost of constructing independent information platform especially for medium to small hospitals, large scale clusters which are based on cloud computing technologies have been very popular to use in order to have a quality information platform that best suits the hospital budget. In this paper, we propose an enhanced model that provides a solution for hospital information systems. This model provides new features that will enhance the efficiency of data retrieval of medical images and the costs of processing these images in the cloud.